Analisis Peran Guru Pendidikan Kewarganegaraan dalam Meningkatkan Minat Belajar Siswa Melalui Inovasi Pembelajaran Berbasis Masalah (Lembaga Pengembangan Kinerja Dosen, 2025)
Teachers have roles and responsibilities that must be carried out in the learning process to educate, direct students. The study aims to analyze the role of Civics teachers in increasing students' interest in learning through problem-based learning innovations at UPTD SMP Negeri 2 Mandrehe Barat. Research method, qualitative method descriptive approach. Data collection techniques: observation, interview, documentation. Informants: principal, Civics teacher, students. Results, conclusions: first, the teacher acts as a facilitator, helping students understand the problem, providing instructions and guiding students to think critically and find solutions to existing problems; second, the obstacles faced, lack of student motivation to follow the learning process, limited learning resources, different student abilities, analyzing problems so that it takes a long time; third, efforts made to overcome obstacles, teachers provide motivation to students, then seek various learning resources by accessing journals, modules, as learning resources.